Avaliação do emprego do pantoprazol na proteção renal em ratos submetidos à lesão renal por isquemia/reperfusão sob anestesia inalatória com isoflurano - Santos, João José Borges de Barros dos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Background and Objective: acute kidney injury (AKI) determines an increase in morbidity and mortality of hospitalized patients. Early diagnosis and the realization of renal protection measures are essential. It was observed that pantoprazole has effect similar to ischemic preconditioning in rat hearts, promoting protective effect. The objective was to analyze the use of pantoprazole in protecting kidneys subjected to ischemia and reperfusion in rats under inhalation anesthesia with isoflurane. Method: forty rats, Wistar male rats, were randomly divided into four groups: RIP (pantoprazole + left renal ischemia), P (pantoprazole), IR (left renal ischemia) and Sham. Renal ischemia time was 20 minutes and reperfusion 30 minutes. The anesthetic technique performed: inhalation anesthesia with isoflurane. The pantoprazole dose was 192 mcg/kg. All animals underwent right nephrectomy and at the end of the experiment proceeded to left nephrectomy for subsequent histological evaluation and classification through tubular necrosis scale. The parameters were: mean arterial pressure (MAP), rectal temperature, the criteria of RIFLE and AKIN, urinary dosage of biomarkers NGAL, KIM-1 and IL-8 and histological evaluation. Serum creatinine was collected in three moments: M1, after monitoring, M2, and M3 after reperfusion, 24 hours after the beginning of the experiment. The urine samples to test for biomarkers occurred before (Urine 1) and after the experiment (Urine 2). The attributes were subjected to statistical analysis and differences were considered statistically significant when p <0,05. Results: significant differences were observed between the groups with application of RIFLE criteria (p=0.007) and AKIN (p=0.003). The PIR and IR groups evolved with higher incidence of AKI. The NGAL and KIM-1 biomarkers increased in all groups throughout the experiment, but with higher values in the PIR and IR groups. IL-18 revealed no group effect (p=0.38) nor the ...

Justificativa e Objetivo: a lesão renal aguda(LRA) determina um aumento na morbidade e na mortalidade de pacientes hospitalizados. O diagnóstico precoce e a realização de medidas de proteção renal são essenciais. Foi observado que o pantoprazol possui efeito similar ao précondicionamento isquêmico em corações de ratos, promovendo efeito protetor. O objetivo deste experimento foi analisar o emprego do pantoprazol na proteção de rins submetidos à lesão de isquemia e reperfusão em ratos sob anestesia geral inalatória com isoflurano. Método: quarenta ratos, Wistar, machos, foram distribuídos aleatoriamente em quatro grupos: PIR (pantoprazol + isquemia artéria renal esquerda), P (pantoprazol), IR (isquemia renal esquerda) e Sham. O tempo de isquemia renal foi de 20 minutos e o de reperfusão, 30 minutos. Anestesia inalatória com isoflurano foi a técnica anestésica realizada. A dose administrada de pantoprazol foi de 192 mcg/kg. Todos os animais foram submetidos à nefrectomia direita e ao final do experimento procedeu-se nefrectomia esquerda, para posterior avaliação histológica e classificação por meio de escala de necrose tubular. Os atributos estudados foram: pressão arterial média (PAM), temperatura retal, os critérios de RIFLE e AKIN, dosagem urinária dos biomarcadores NGAL, KIM-1 e IL-8 e avaliação histológica. A creatinina sérica foi coletada em três momentos: M1, após monitorização; M2, após a reperfusão; e M3, 24 horas após o inicio do experimento. As coletas de urina para dosagem dos biomarcadores ocorreram antes (Urina 1) e após o experimento (Urina 2). Os atributos foram submetidos à análise estatística e as diferenças foram consideradas estatisticamente significativas quando p<0,05. Resultados: diferenças estatisticamente significativas foram observadas entre os grupos com aplicação dos critérios de RIFLE (p=0,007) e AKIN (p-0,003). Os grupos PIR e IR evoluíram com maior incidência de...
Pantoprazole employment evaluation for renal protection in rats submited to renal ischemia/reperfusion under inhalation anesthesia with isoflurane
Keywords: Rins - Doenças; Insuficiência renal aguda; Isquemia; Marcadores bioquímicos; Farmacologia; Reperfusão (Fisiologia); Reperfusion (Physiology); Ischemia